ETIKA DALAM MANAJEMEN PENDIDIKAN DAN PELATIHAN (DIKLAT) - Zulqaidah; Abdul Fattah Nasution; Dian Pratiwi br. Marpaung; Nurroyian (Cendekia Madani Nusantara, 2024)
Ethics in education and training has an important role in forming individual character, morals and discipline, especially for teachers and educators. This research aims to examine ethics in education and training management (Diklat), ethics in education and training management, principles of education and training (diklat). This research uses a qualitative approach, which is also a literature study or library research method. Library research, also known as library research, is a type of research that involves collecting library data through a systematic process to collect, process, and summarize information with the aim of finding solutions to problems related to literature. This research approach is in line with previous research which used a library institution approach. Before reviewing library materials, researchers must know exactly where they will get scientific information from. The research results illustrate that ethics in education and training management is that the application of ethical principles is very important to create an educational environment that is fair, effective, and supports the development of all parties involved. Ethics in education and training management includes honesty, integrity, fairness, and professionalism, all of which contribute to transparency and trust in the educational process.